Feasibility of selective salvage neck dissection (level II, III, IV) after primary radiotherapy of pharynx and larynx squamous cell carcinoma - Abdullah, Kahairi; I, Bing Tan; van den Brekel, Michiel; M, Baris Karakullukcu (2014)
Background Traditionally, radical or modified radical neck dissection was performed as salvage procedure in persistent or recurrent neck disease after primary radiotherapy. This relatively radical procedure has produced lots of morbidity to the survivors.